Innate Lymphoid Cells and Celiac Disease: Current PerspectiveSummary - Xuechen Yu; Justin Vargas; Peter H.R. Green; Govind Bhagat (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Celiac disease (CD) is a common autoimmune disorder triggered by the ingestion of gluten in genetically susceptible individuals. Although the mechanisms underlying gliadin-mediated activation of adaptive immunity in CD have been well-characterized, regulation of innate immune responses and the functions of certain immune cell populations within the epithelium and lamina propria are not well-understood at present. Innate lymphoid cells (ILCs) are types of innate immune cells that have lymphoid morphology, lack antigen-specific receptors, and play important roles in tissue homeostasis, inflammation, and protective immune responses against pathogens. Information regarding the diversity and functions of ILCs in lymphoid organs and at mucosal sites has grown over the past decade, and roles of different ILC subsets in the pathogenesis of some inflammatory intestinal diseases have been proposed. However, our understanding of the contribution of ILCs toward the initiation and progression of CD is still limited. In this review, we discuss current pathophysiological aspects of ILCs within the gastrointestinal tract, findings of recent investigations characterizing ILC alterations in CD and refractory CD, and suggest avenues for future research.